Properties of the protein encoded by the UL32 open reading frame of herpes simplex virus 1. - Chang, Y E (1996)
The functions previously assigned to the essential herpes simplex virus 1 UL32 protein were in cleavage and/or packaging of viral DNA and in maturation and/or translocation of viral glycoproteins to the plasma membrane. The amino acid sequence predicts N-linked glycosylation sites and sequences conserved in aspartyl proteases and in zinc-binding proteins. We report the following. (i) The 596-amino-acid UL32 protein accumulated predominantly in the cytoplasm of infected cells but was not metabolically labeled with glucosamine and did not band with membranes containing a known glycoprotein in flotation sucrose density gradients. The UL32 protein does not, therefore, have the properties of an intrinsic membrane protein. (ii) Experiments designed to demonstrate aspartyl protease activity in a phage display system failed to reveal proteolytic activity. Moreover, substitution of Asp-110 with Gly in the sequence Asp-Thr-Gly, the hallmark of aspartyl proteases, had no effect on viral replication in Vero and SK-N-SH cell lines or in human foreskin fibroblasts. Therefore, if the UL32 protein functions as a protease, this function is not required in cells in culture. (iii) Both the native UL32 protein and a histidine-tagged UL32 protein made in recombinant baculovirus-infected insect cells bound zinc. The consensus sequence is conserved in the UL32 homologs from varicella-zoster virus and equine herpesvirus 1. UL32 protein is therefore a cysteine-rich, zinc-binding essential cytoplasmic protein whose function is not yet clear.